Exploring the impact of media literacy instruction and video projects in a college technology course - Genereux, William E. (Kansas State University, 2015)
This study explored the impact of requiring a video term-paper project and media literacy instruction to address the desired educational goals of increasing student ownership of learning, learning course-related concepts, providing evidence of communication skills, and increasing knowledge of key media literacy concepts. Study participants came from convenience samples drawn from a technology course taught by the researcher and from a writing course taught by a colleague. The sixty participants were male (41) and female (19) college students in different years of their courses of study. Participants comprised traditional-age (18-24) and non-traditional-age (25+) students possessing varying levels of familiarity with the skills examined. A quasi-experimental, two-group control/intervention design was used, augmented by additional data collected from the intervention group. The quasi-experiment consisted of pre-and post-test measurements of media literacy, with both groups receiving media literacy instruction an intervention in the form of a video term-paper research project completed by the intervention group. Additional data were gathered from student surveys and interviews conducted with the intervention group. The quasi-experiment did not provide evidence that either the media literacy instruction or the video term-paper project increased knowledge of media-literacy concepts. However, the data collected indicated that the video project was a relevant challenge that engaged students in active participation in their learning. Despite the inherent difficulties in the use of writing and communications skills in technology classes, science and technology educators should investigate the benefits of using media projects in their courses.
Keywords: Video projects; Media literacy; Literacy; Education; Information technology; Teaching; Education, General (0515); Education, Technology (0710); Higher Education (0745)